Observations of the development of Xanthoria farinosa under optical and electron microscopy - García, Renato; Rosato, Vilma (Taylor & Francis, 2017)
Xanthoria farinosa is a foliose lichen widely distributed in South America, growing not only on rocks but also on man-made structures. This species has abundant soralia, but it is unknown how development occurs from the soredium to the formation of a complete thallus. The soredia were extracted from the thallus with forceps, planted on glass plates and exposed to outdoor conditions for a period of 24 months; in every 3 months, optical inspection was performed with a stereomicroscope and a compound microscope, in addition, four samples with different exposure times were chosen to observe under a scanning electron microscope. The development of hyphae and the adhesion of these to the substrate, and the outlines of the formation of the lobules and rhizines could be observed. Our study is a first attempt to understand the development of this species which is endemic to South America and very common in the area.
Keywords: Lichen; Outdoor; Soralia; Glass; Adhesion to the substrate; Lobe formation